Structural transition on Pb1-xSrxTiO3 produced by chemical method - Leal, S. H.; Escote, M. T.; Pontes, Fenelon Martinho Lima [UNESP]; Leite, E. R.; Joya, M. R.; Pizani, P. S.; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (Elsevier B.V. Sa, 2009)
Polycrystalline Pb1-xSrxTiO3 (PST) compounds were synthesized through the polymerization of complex precursor method. They were characterized by X-ray diffraction (XRD), Raman spectroscopy, thermal analysis and scanning electron microscopy (SEM). These characterizations revealed that all samples were single-phase, with no trace of intermediate phase reflections. A tetragonal-cubic phase transition at room temperature was observed for Sr content ranging from x similar to 0.6 to 0.7. Similar results were also observed by means of Raman spectroscopy and confirmed by the analysis of this transition by thermal analysis. Such results suggested that this synthesis method is comparable to other methods described in the literature for the production of high-quality PST compounds and chemical homogeneity. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Powders; Chemical synthesis; Phase transition